Amino‐Containing Ultrafine Organosilica‐Nanoparticle‐Modified Au Electrode for the Determination of Cu(II) Ions. Issue 11 (18th October 2013) - Wu, Zhongwei; Liao, Jinjin; Xiao, Jianlin; Liu, Jianyun; Yang, Jianmao; Zhou, Xin; Xin, Meng
Abstract Using 3‐Aminopropyltriethoxysilane(APTES) as a single silica source, an amino‐rich ultrafine organosilica‐nanoparticle‐modified Au electrode was fabricated, following the formation of (3‐mercaptopropyl)‐trimethoxysilane (MPTS) monolayer on Au surface (MPTS/Au). With cetyltrimethylammonium bromide as an additive, APTES‐based gel particles on the electrode have a narrow particle size distribution of 4–7 nm and "crystal‐like" structure. AFM and electrochemical characterization confirmed the successful grafting of APTES nanoparticles on MPTS/Au. The APTES/MPTS/Au electrode is highly sensitive for the detection of copper(II) ions with a detection limit as low as 1.6×10−12 mol L−1 (S/N>3) by square wave voltammetry. The current is linear to copper(II) concentration between 1.6×10−12 and 6.25×10−10 mol L−1.